2022
DOI: 10.48550/arxiv.2201.01492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FAVER: Blind Quality Prediction of Variable Frame Rate Videos

Abstract: Video quality assessment (VQA) remains an important and challenging problem that affects many applications at the widest scales. Recent advances in mobile devices and cloud computing techniques have made it possible to capture, process, and share high resolution, high frame rate (HFR) videos across the Internet nearly instantaneously. Being able to monitor and control the quality of these streamed videos can enable the delivery of more enjoyable content and perceptually optimized rate control. Accordingly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Previous studies evaluate the video quality either using the original spatial resolution or a fixed resized spatial resolution, which ignore that videos are naturally multi-scale [41]. Some existing work [30][20] [16] shows that considering the multi-scale characteristics can improve the performance of image quality assessment.…”
Section: Multi-scale Quality Fusion Strategymentioning
confidence: 99%
“…Previous studies evaluate the video quality either using the original spatial resolution or a fixed resized spatial resolution, which ignore that videos are naturally multi-scale [41]. Some existing work [30][20] [16] shows that considering the multi-scale characteristics can improve the performance of image quality assessment.…”
Section: Multi-scale Quality Fusion Strategymentioning
confidence: 99%
“…We employ temporal band-pass transforms inspired by similar successes [23], [24], [38], [67], [68] capturing temporal distortions. Temporal band-pass coefficients demonstrate reliable statistical regularities on very high quality videos, but these are predictably disturbed by the presence of distortions.…”
Section: Multiscale Learning and Temporal Transformationsmentioning
confidence: 99%
“…VFR-VQA is a challenging problem, since quality predictors must account for subtle perceptual quality changes occuring along the temporal dimension due to frame rate changes. As comparisons we also included FAVER [68], which is a current SOTA no-reference VFR-VQA model. From Table V, it may be observed that CONVIQT achieved competitive performance when compared against other NR-VQA models, indicating the frame rate discrimination capability of CONVIQT representations.…”
Section: Performance Comparison On Variable Frame Rate Videosmentioning
confidence: 99%
“…More recently, machine learning techniques have been employed in the development of perceptual metrics including VMAF [15], C3DVQA [17] and CONTRIQUE [65]. Alongside these generic quality metrics, assessment methods that were designed to specifically model the effect of frame rate/spatial resolution down-sampling or frame interpolation have been reported, including FRQM [66], ST-GREED [67], VSTR [68], FAVER [69] and FloLPIPS. However, none of these methods have been rigorously benchmarked due to the lack of databases with diverse content and ground-truth metadata.…”
Section: B Objective Quality Assessment For Vfimentioning
confidence: 99%
“…For completeness, we have also considered no-reference (NR) quality metrics. These include image models, NIQE [101] and deepIQA-NR [99], and video models, VIIDEO [102], VBLIINDS [103], VIDEVAL [104], RAPIQUE [105], and FAVER [69].…”
Section: Evaluation Of Objective Quality Metricsmentioning
confidence: 99%